Pengelolaan Ketidaknyamanan Pasca Partum pada Ibu Post Partum Spontan dengan Episiotomy: Management of Post Partum Discomfort in Spontaneous Post Partum Mothers with Episiotomy - Laelatul Saadah; Siti Haryani (Journal of Holistics and Health Sciences (JHHS), 2022)
Post partum is the period after childbirth or called the puerperium, this period is the period after childbirth which is needed for the recovery of the uterus which lasts 6 minutes. The action of episiotomy causes in the perineal area which will cause postpartum discomfort in the wounds form of pain at the stitches in the perineum. Postpartum discomfort is an uncomfortable feeling associated with conditions after childbirth. This writing aims to find out the describe the management of postpartum discomfort in spontaneous postpartum mothers. The writing method used in this preparation uses a descriptive method with a case study design using documentation data collection techniques. The data collection technique was carried out with a nursing methodological approach, including assessment, diagnosis, intervention, implementation and nursing evaluation. Management of post partum discomfort nursing care for 3 days. Actions taken to overcome the problem of postpartum discomfort are pain management and perineal care, by means of deep breathing relaxation and vulva hygiene. Based on the nursing actions taken, it can be concluded that postpartum discomfort can be resolved with the patient saying he no longer feels pain and is more comfortable with a pain scale of 1. Patients are expected to be able to perform perineal care and pain management in an appropriate and correct manner in accordance with what has been taught to anticipate the problem of post partum discomfort in spontaneous postpartum mothers. ABSTRAK Post partum adalah masa sesudah persalinan atau disebut masa nifas, masa ini adalah masa sesudah persalinan yang diperlukan untuk pulihnya kembali alat kandungan yang lamanya 6 minggu. Tindakan episiotomy menyebabkan luka di daerah perineum akan menyebabkan ketidaknyamanan pasca partum berupa nyeri pada luka jahitan di perineum. Ketidaknyamanan pasca partum adalah perasaan tidak nyaman yang berhubungan dengan kondisi setelah melahirkan. Penulisan ini bertujuan untuk mengetahui gambaran pengelolaan ketidaknyamanan pasca partum pada ibu post partum spontan. Metode penulisan yang digunakan penyusunan ini menggunakan jenis metode deskriptif dengan rancangan studi kasus menggunakan teknik pengumpulan data dokumentasi. Teknik pengumpulan data dilakukan dengan pendekatan metodologi keperawatan, meliputi pengkajian, diagnosis, intervensi, implementasi dan evaluasi keperawatan. Pengelolaan asuhan keperawatan ketidaknyamanan pasca partum selama 3 hari. Tindakan yang dilakukan untuk mengatasi masalah katidaknyamanan pasca partum adalah manjemen nyeri dan perawatan perineum, dengan cara relaksasi nafas dalam dan vulva hygiene. Berdasarkan tindakan keperawatan yang dilakukan, maka dapat disimpulkan ketidaknyamanan pasca partum dapat teratasi dengan pasien mengatakan sudah tidak merasakan nyeri dan lebih nyaman skala nyeri 1. Pasien diharapkan dapat melakukan tindakan perawatan perineum dan manajemen nyeri dengan cara yang tepat dan benar sesuai dengan apa yang telah diajarkan untuk mengantisipasi permasalah Ketidaknyamana pasca partum pada ibu post partum spontan.